Comparison Of Local And Import Sands Quality Laboratory Tests Results For Used In Hydraulic Fracturing Operations - Tjuwati M; Panca Wahyudi; Supriyatno Supriyatno (Scientific Contributions Oil and Gas, 2008)
Sand quality laboratory tests have been carried out on local and import uncoated sands. Based on results of sand sieve, roundness, sphericity, turbidity, acid solubility and crush resistance at 3000 psi quality tests of import uncoated sand has better quality than local sand. The import sand fulfills API – RP 56 specification requirements and will be able used in hydraulic fracturing operation. Whereas, the local uncoated sand does not achieve API - RP 56 specification requirements.